2014
DOI: 10.1007/s11524-014-9899-y
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Cocaine Prices and Purity with Trends in Emergency Department Visits in a Major Metropolitan Area

Abstract: Illicit drug use not only causes acute and chronic adverse health outcomes but also results in a significant burden to health care providers. The objective of this study is to examine the relationship between cocaine prices and purity with emergency department (ED) visits for the Chicago-Naperville-Joliet metropolitan area. Our primary outcome was number of cocaine-related ED visits per quarter provided by the Drug Abuse Warning Network. The predictor variables of cocaine purity and price were provided by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In this study cocaine co-detections had the largest increase of any co-detected substance, with 34% more cases reported in 2020 than in 2013. The purity of both powder and crack cocaine has concurrently risen in the United Kingdom (PHE, 2021), and a positive correlation between cocaine purity and emergency department visits has been observed (Zhu et al., 2014), which may explain in part the rise in fatalities with cocaine co-detections.…”
Section: Discussionmentioning
confidence: 99%
“…In this study cocaine co-detections had the largest increase of any co-detected substance, with 34% more cases reported in 2020 than in 2013. The purity of both powder and crack cocaine has concurrently risen in the United Kingdom (PHE, 2021), and a positive correlation between cocaine purity and emergency department visits has been observed (Zhu et al., 2014), which may explain in part the rise in fatalities with cocaine co-detections.…”
Section: Discussionmentioning
confidence: 99%
“…That is, increased PAP is associated with lower harm, and reduced PAP is associated with increased harm. All exceptions can be explained by the price series failing to adjust for purity (eg Zhu et al 2014) or the study's focus on outcomes for which theory predicts effects may differ (eg treatment). In that regard, consistent with economic theory, there were subtle differences in outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Five US studies examined the relationship between price, purity and PAP and ED admissions. All except one (which did not employ PAP: Zhu et al (2014)) found an inverse relationship between PAP and ED admissions (Table A1). This means an increase in PAP was associated with a reduction in ED admissions.…”
Section: Health Outcomesmentioning
confidence: 99%
“…Forty-six drugs were analyzed against NADAC in this process ( Supplementary Table 2) and split into categories of drug type (Supplementary Table 1). Other drugs did not share similar NADAC names and/or did not have sufficient longitudinal data to build statistical power even though they did qualify as n > 30 [19]. These drugs were not included in the analysis.…”
Section: Methodsmentioning
confidence: 99%